The Effect of Baby Gym Complementary Therapy on Motor Skills in Improving Baby Development - Arintasari, Farida; Ian Rossalia Pradita Puteri (Poltekkes Kemenkes Tasikmalaya, 2025)
Background: Globally, around 20-40% of infants aged 0-2 years experience problems with delays in the development process. The period from infancy to age 2 years is called the 1000 days of birth. This period is the shortest of all developmental periods, so it is essential to meet optimal nutrition and stimulus because, after this period is passed, the brain will grow slowly and can never grow quickly again. Baby massages can help children get the appropriate stimulation for infant development. Baby massage is one of the traditions inherited from our ancestors, and it has proven its efficacy in stimulating development. Along with technological development, baby massage has been modified to a more modern pattern until it became a new trend known as the baby gym. This study aims to determine the effectiveness of complementary baby gym therapy on motor skills in improving development. The research method used is quantitative research with a quasy experiment design with pre-test and post-test control group design. The sample in this study were toddlers aged 5-12 months. The sample size was 60 toddlers, 30 in the experimental and 30 in the control group. The sampling technique was purposive sampling. Results: After complementary baby gym therapy was carried out on babies, the baby's motor development was normal for 86.67% of respondents. The t-test results showed p = 0.012 (<0.05), meaning that there is a significant influence between the baby gym and the development of motor babies. Conclusion: Complementary therapy in the baby gym has an effect on motor skills and on improving development.